Penerapan model discovery learning berbantuan e-LKPD untuk meningkatkan kemampuan komunikasi matematis siswa kelas X MA pada materi SPLTV - Rezki Adelima Lubis; Nelly Fitriani; Ratna Sariningsih (IKIP Siliwangi, 2023)
This study aims to obtain a description of the application of the e-LKPD assisted discovery learning model in an effort to improve students' mathematical communication abilities and to find out differences in students' mathematical communication abilities before and after being given treatment with the e-LKPD assisted discovery learning model for class X MA Miftahul 'Ulum on SPLTV material. The sample in this study was students of class X IPA MA Miftahul 'Ulum with a total of 10 students. The method used in this research is experimental research with the instrument used is a test of mathematical communication ability. Data analysis was carried out using the Pre-Experimental Design method in the form of One Group Pretest-Posttest Design. The results showed that there was an influence of the e-LKPD-assisted discovery learning model on students' mathematical communication abilities, seen in the results of data analysis with Ltest <Ltable 5%, which means that there were differences in students' mathematical communication abilities before and after treatment of e-assisted discovery learning models. LKPD on SPLTV material.